(untitled) (Harlow, United Kingdom, 2016)
The introductory chapters have been restructured to more logically fit with teaching. Several new exercises have been introduced, as well as fuller solutions to existing ones. More coverage of the history of mathematical and economic ideas has been added, as well as of the scientists who developed them. New example based on the 2014 UK reform of housing taxation illustrating how a discontinuous function can have significant economic consequences. The associated material in MyMathLab has been expanded and improved.
Keywords: Kinh tế, toán học,Economics, Mathematical